FAKTOR - FAKTOR YANG MEMPENGARUHI PERMINTAAN KOMODITAS TOMAT DI KECAMATAN MAESAAN KABUPATEN MINAHASA SELATAN - Endey, Metry Syuli; Pangemanan, Paulus Adrian; Porajouw, Oktavianus (Sam Ratulangi University, 2022)
This study aims to analyze the factors that influence the demand for tomatoes in Maesaan District, South Minahasa Regency. This research was conducted in Maesaan District, South Minahasa Regency. The research was carried out for 3 months, starting from June to August. This study uses two types of data sources, namely primary and secondary data. Primary data was obtained by means of direct interviews with tomato consumers in the market. Meanwhile, secondary data was obtained through related institutions and previous research journals. Sampling in this study using a method (convenience sampling) which is to collect information from members of the population, the number of which is used as a sample is 30 tomato consumers. The variables studied in this study were the price of tomatoes, the level of income, the price of complementary goods and the number of family members. The analytical model used to estimate the factors that influence the demand for tomatoes in this study is multiple linear regression analysis. Based on the results of research on the factors that influence the demand for tomato commodities in Maesaan District, it can be concluded that prices and income significantly affect the demand for tomatoes, while the price of complementary goods and the number of family members do not affect the demand for tomatoes in Maesaan District.